Wayang Beber Lakon “Joko Kembang Kuning” Garap Kontemporer Sebagai Upaya Pelestarian Dan Pengembangan Seni Tradisi - Suratno Suratno; Jaka Rianto (Institut Seni Indonesia Surakarta, 2019)
The writting aims at describing the model consept of script writting on wayang beber‘s performance on contemporary approach as the way to do preservation and cultivation of the tradisional performing art which is nowday almost extinct. This model consept of script writting will be clarified through how to treat the character of Panji Asmarabangun and Sekartaji as the main characters in the story of “Joko Kembang Kuning”. The clarification will be answering the questions on: (1) how is the synopsis; (2) how is the structure of scenes; (3) How is the course of story and the progress of dramatics; and (4) how is the characteristic of each character on the story.